PHYSICAL EDUCATION ESSENTIALLY IN FINNISH SCHOOL SYSTEM AND IN NORMAL LYCEUM OF HELSINKI (Fiep Bulletin - online, 2014)
This paper presents system of physical education in Normal Lyceum of Helsinki. It is based on Constructivist view of learning. It allows students in very independent way to choose different kinds of physical activities, and make a special program of physical education.There are physical courses common to all students and elective courses.
Keywords: physical education; constructivist learning; Finnish school system; curriculum